Investigation of Quantum Dot Color Filter Micro-LED Display - Xuhui Peng; Yang Zeng; Sitao Huo; Zhenyuan Yang; Xiaoping Huang; Qing Zhao (Photonic Sensors, 2023)
Abstract In this work, we present the investigation of the quantum dot color filter (QDCF) micro-light emitting diode (micro-LED) display. Green and red quantum dot photoresist (QDPR) materials are patterned into a pixelated array and precisely bonded with an all-blue micro-light emitting diode (micro-LED) substrate, forming a red, green, and blue (RGB) full color display through color conversion. A few factors that influence the achievable color gamut are further investigated. The resulting 1.1-inch 228-pixels per inch (ppi) display demo shows the good performance. The findings in this paper pave a way to the future industrialization of the micro-LED display.